The link between HR practices, psychological contract fulfilment, and organisational performance in Greece: An economic crisis perspective - Anastasia A. Katou (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This study examines the impact of HR practices on organizational performance through the mediating role of psychological contract (expressed by the influence of employer on employee promises fulfilment through employee attitudes) and further examines whether this relationship remains stable during periods of external economic crisis. Methodology: The analysis is based on structural equation modelling using two national samples of a two time study of Greek private and public organizations in the manufacturing, services and trade sectors. The first data collection took place in 2008 (treated as a control period) and the second in 2010 (treated as an economic crisis period). Findings: The study is providing proof that the employee attitudes of satisfaction, commitment and motivation, constitute a nested mediating epicentre of the HR practices - organizational performance relationship, meaning that employee attitudes are positively influencing employee promises fulfilment and organizational performance and being positively influenced by employer promises fulfilment and HR practices. Research limitations/implications: Although data was collected using the same questionnaire at the two time periods of 2008 and 2010, the design of the study is not longitudinal. As a result, the study does not allow for dynamic causal inferences. Value: The study supports the view that although the structure of the relationship between HR practices and organizational performance does not change in periods of economic crisis, the strength of this structure is weaker compared to normal economic periods. Additionally, this study provides a greater understanding of the process by which psychological contract mediates the relationship between HR practices and organizational performance, with special reference to economic crisis.
Keywords: 650; HR practices; psychological contract; employee attitudes; organizational performance; economic crisis